Effects of traumatic brain injury on sleep and enlarged perivascular spaces. Issue 11 (November 2019) - Opel, Ryan A; Christy, Alison; Boespflug, Erin L; Weymann, Kristianna B; Case, Brendan; Pollock, Jeffery M; Silbert, Lisa C; Lim, Miranda M
Clearance of perivascular wastes in the brain may be critical to the pathogenesis of amyloidopathies. Enlarged perivascular spaces (ePVS) on MRI have also been associated with amyloidopathies, suggesting that there may be a mechanistic link between ePVS and impaired clearance. Sleep and traumatic brain injury (TBI) both modulate clearance of amyloid-beta through glymphatic function. Therefore, we sought to evaluate the relationship between sleep, TBI, and ePVS on brain MRI. A retrospective study was performed in individuals with overnight polysomnography and 3T brain MRI consented from a single site ( n = 38). Thirteen of these individuals had a medically confirmed history of TBI. ePVS were visually assessed by blinded experimenters and analyzed in conjunction with sleep metrics and TBI status. Overall, individuals with shorter total sleep time had significantly higher ePVS burden. Furthermore, individuals with TBI showed a stronger relationship between sleep and ePVS compared to the non-TBI group. These results support the hypothesis that ePVS may be modulated by sleep and TBI, and may have implications for the role of the glymphatic system in ePVS.